KONSEP RADD DALAM KOMPILASI HUKUM ISLAM - Billah, Mu'tashim (Ahkam: Jurnal Hukum Islam, 2021)
This research purposed to reveal the main concept of radd used in Indonesian Law according to KHI 193. This article focused on rights of a husband or a wife on radd and balanced distribution based on the opinion of Religious Court of Yogyakarta. This is a field research that used judges from Yogyakarta’s Religion Court as responden. This is a normative-descriptive research, with the theory of legal finding and legal interpretation to discuss the opinions of judges. The result of this research shows that (based on KHI 193) there are two interpretations of radd. First, either a husband or a wife should get the excess share of inheritance based on many interpretations. Grammatically, there is no exception for a husband or wife to get the excess share. Analogically, they have the rights on radd because it is equated with the concept of ‘aul, where husband and wife’s rights are reduced. Historically, judges accomodates the opinion of Uṡman who gave the spouses the right of share excess. Second, spouses have no right on excess share. Historically, there was an ijtihad made by jumhur considered that marital relationship ended by the decease of spouse. They accomodate the balanced distribution means that excess share is distributed proportionally based on each part.